Interactions between Extractant Molecules: Organic-Phase Thermodynamics of TALSPEAK–MME. Issue 1 (2nd January 2017) - Johnson, Aaron; Alvarez, Joel; Nash, Kenneth L.
ABSTRACT: To reduce the cost and complexity of separations for closed nuclear fuel cycles, solvent extraction processes based on combined solvating and cation exchange extractants are being considered. One such process, Trivalent Actinide Lanthanide Separations using Phosphorus Extractants and Aqueous Komplexes–Mixed Monofunctional Extractants (TALSPEAK–MME), that combines the neutral extractant Cyanex-923 and cation exchanging extractant 2-ethyl(hexyl)phosphonic acid mono-2-ethyl(hexyl) ester (HEH[EHP]) has shown considerable promise. However, little knowledge of the underlying chemistry of this process has been reported. In this report, 31 P NMR and FT-IR spectroscopies have been used to investigate organic-phase extractant interactions. A 1:1 adduct between Cyanex-923 and HEH[EHP] has been identified. The equilibrium constant describing the formation of this adduct (log K ) has been determined to be between 2.04 and 2.21, signifying relatively weak interactions between the extractants. In parallel, it has been determined that the presence of this adduct does not change the nitric acid extraction mechanism observed by Cyanex-923; its presence merely reduces the free concentration of Cyanex-923 available to extract nitric acid thus slightly reducing the total acid partitioned to the organic phase. These findings were used to calculate an extractant speciation diagram for TALSPEAK–MME, the results of which were used to improve understanding of the metal ion extraction behavior observed in this system.